Construction of mathematical model of the drying process polyethylene terephthalate granulate - Надолинський, Олександр Володимирович; Коваленко, Ігор Валентинович (Technology audit and production reserves, 2014)
The paper presents the results of experiments on the optimum conditions of the drying process of PET granulate. The results of experiment on isothermal drying of granules are presented. It is necessary for the management mode for drying the granules and further processing. The results of designed of research show that the process of drying the PET granulate is nonlinear. Thus there is structural alteration of polymer which accompanies the deep (to 0,005%) moving away of moisture from him, that predetermines stability of further technological process. After the analysis of experiments, we concluded that to achieve the desired moisture content must be chough four hours of drying process. The mathematical model of the process of drying the granulate based on multivariate experiment indicates that the greatest influence on the drying process have such factors as: the time of process passage, the drying temperature and the grain diameter of the material. Established during the experiment to the optimum drying mode (temperature and time of the process) that will help in saving energy and material resources for companies operating in this area.